KONTRIBUSI ETIKA BISNIS ISLAM, LOYALITAS PELANGGAN DAN SERVICE QUALITY ISLAMIC TERHADAP KEPUASAN KONSUMEN - Ana Kurnia Ashari; Nur Anim Jauhariyah (Program Studi Ekonomi Syariah, STAI AN-NAJAH INDONESIA MANDIRI, 2024)
Islamic Business Ethics, Customer Loyalty, and Islamic Service Quality have a very important role in increasing customer satisfaction, especially in the context of a business based on Islamic values. The purpose of this study was to analyze the contribution of the influence of Islamic business ethics, Customer Loyalty, and Islamic service quality to customer satisfaction at the Ausath Mart Darussalam Blokagung Store. The study used a quantitative approach on 81 respondents who were regular customers of the store. The results of the analysis showed that Islamic Business Ethics, Customer Loyalty, and Islamic Service Quality had a significant effect on Customer Satisfaction at the Ausath Mart Darussalam Blokagung Store. The results of the regression test showed that Islamic Business Ethics had a sig. value of 0.032 <0.05; Customer Loyalty had a sig. value of 0.033 <0.05 and Islamic Service Quality had a sig. value of 0.005 <0.05. The amount of contribution of these variables was 30.5% while the remaining 69.5% was influenced by other variables not explained in this study. The combination of implementing strong Islamic business ethics, increasing customer loyalty, and quality of service oriented towards Islamic values, as a whole, is able to create a satisfying shopping experience for consumers. This proves that the three variables simultaneously contribute to forming consumer satisfaction and sustainable loyalty. Keywords: Islamic Business Ethics, Customer Loyalty, Islamic Service Quality, Consumer Satisfaction